The use of insects in forensic investigations: An overview on the scope of forensic entomology - Joseph, Isaac (Medknow Publications & Media Pvt Ltd, 2011)
Forensic entomology is the study of insects/arthropods in criminal investigation. Right from the early stages insects are attracted to the decomposing body and may lay eggs in it. By studying the insect population and the developing larval stages, forensic scientists can estimate the postmortem index, any change in position of the corpse as well as the cause of death. Forensic odontologists are called upon more frequently to collaborate in criminal investigations and hence should be aware of the possibilities that forensic entomology have to offer and use it as an adjunct to the conventional means of forensic investigation.